ANTITYPE OF JESUS CHRIST BEYOND THE TYPE OF MELCHIZEDEK ON HEBREWS - Paulus JinuKim (SAINT PAUL'S REVIEW, 2021)
In Hebrews, the High Priest theory has a very fundamental and important position in the structure of the entire Hebrews. It can be said that it plays a central role in its quantity and content in the whole text. The words of Ellingworth are quite reasonable, “Perhaps the Hebrews author's idea of ??Christ is very likely to be two central pillars, the ‘Son of God’ (1: 2) and ‘High Priest’ (2:17).”[1] In particular, the idea that Christ in the high priesthood of Jesus Christ is a high priest following the order of Melchizedek is at the heart of the High Priesthood. Because the text of the book of Hebrews emphasizes Jesus Christ as a very different high priest who follows the order of Melchizedek directly and very repeatedly.[2] The texts of the high priesthood of Jesus Christ show the concept that Jesus is the only unique, special, and superior follower of the order of Melchizedek. Therefore, Melchizedek is an essential element in understanding the duty of the High Priest of Jesus Christ.